User Experience of Cognitive Digital Games Among Elderly People to Prevent Dementia - Khairunisa, Yuyun; Latif, Antinah; Nurwicaksono, Bayu Dwi; Kuswoyo, Deni (Politeknik Negeri Bengkalis, 2024)
A few ponders have appeared that cognitive and physical work out can offer assistance diminish the hazard andindications of alzheimer's and dementia. The utilize cognitive technology can be an successful to anticipate or moderate themovement of alzheimer's and dementia. Creator past inquire about have created a crosswords memory diversion applicationwith manufactured insights highlights as a refresher as one of the reviving media for cognitive treatment for the elderly .Research was conducted to test the user experience among users, namely the pre-elderly and elderly community. The researchwas conducted on 30 elderly people at the elderly posyandu. UX encompasses all user experiences and interactions with aproduct, service, or brand. It includes the user's feelings, emotions, and context when interacting. In this case, what is evaluatedis the ease of navigation in playing games, whether this game is interesting and fun and whether there are less pleasantexperiences. The result is for the convenience of navigation has a UX score of 68.42% out of a maximum of 100%, while theassessment for the fun experience of playing this game is 76.8%. The less pleasant experience is if there is a process ofinstalling the game on a mobile device because it is quite troublesome so it needs a mentoring process. And the font sizegreatly affects the comfort of using the application, where the larger the font size, the better.